2014
DOI: 10.1093/jat/bku012
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Method for the Determination of Total Bisphenol A at Trace Levels in Human Blood and Urine and Elucidation of Factors Influencing Method Accuracy and Sensitivity

Abstract: This publication describes a method for the determination of total bisphenol A (BPA and conjugated BPA) following enzyme hydrolysis and is intended as a companion to our previously developed analytical method for the determination of free BPA (the aglycone) in human blood and urine using high-performance liquid chromatography-tandem mass spectrometry ( 1). That free BPA method provided a means to account for and/or eliminate background contamination and demonstrated accuracy and reproducibility in both matrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Various options in the software were tested for optimal analysis in which selection of appropriate peak smoothing significantly improved detection limit of non-derivatized E2. A weighting factor of 1/x was applied to the data (Markham et al, 2014;Vitku et al, 2015) and the linearity of the standard curves was evaluated using correlation coefficient. Coefficient of variations (CV), defined as the ratio of the standard deviation to the mean and represented as a percentage, was used to express the precision and repeatability of the analyses (Blue et al, 2018;Gaikwad, 2013).…”
Section: Methods Validation Accuracy Calculation and Data Analysismentioning
confidence: 99%
“…Various options in the software were tested for optimal analysis in which selection of appropriate peak smoothing significantly improved detection limit of non-derivatized E2. A weighting factor of 1/x was applied to the data (Markham et al, 2014;Vitku et al, 2015) and the linearity of the standard curves was evaluated using correlation coefficient. Coefficient of variations (CV), defined as the ratio of the standard deviation to the mean and represented as a percentage, was used to express the precision and repeatability of the analyses (Blue et al, 2018;Gaikwad, 2013).…”
Section: Methods Validation Accuracy Calculation and Data Analysismentioning
confidence: 99%
“…The BPA standard for sample fortification of the total BPA analysis was prepared in H 2 O, with an MeCN share of ≤ 0.2% (v/v) in the sample‒buffer solution, aimed to prevent the denaturation of β-glucuronidase as in Markham et al ( 2014 ), who demonstrated that the enzyme viability is affected at the organic solvent level of > 0.5% (v/v), particularly at lower concentrations of the analyte (< 2 ng/mL).…”
Section: Discussionmentioning
confidence: 99%